New Trends in Aryl Hydrocarbon Receptor Biology - Mulero-Navarro, Sonia; Fernandez-Salguero, Pedro M. (Frontiers in Cell and Developmental Biology, 2016)
Traditionally considered as a critical intermediate in the toxic and carcinogenic response to dioxin (2,3,7,8-tetrachlorodibenzo-p-dioxin, TCDD), the Aryl hydrocarbon/Dioxin receptor (AhR) has proven to be also an important regulator of cell physiology and organ homeostasis. AhR has become an interesting and actual area of research mainly boosted by a significant number of recent studies analyzing its contribution to the proper functioning of the immune, hepatic, cardiovascular, vascular and reproductive systems. At the cellular level, AhR establishes functional interactions with signaling pathways governing cell proliferation and cell cycle, cell morphology, cell adhesion and cell migration. Two exciting new aspects in AhR biology deal with its implication in the control of cell differentiation and its more than likely involvement in cell pluripotency and stemness. In fact, it is possible that AhR could help modulate the balance between differentiation and pluripotency in normal and transformed tumor cells. At the molecular level, AhR regulates an increasingly large array of physiologically relevant genes either by traditional transcription-dependent mechanisms or by unforeseen processes involving genomic insulators, chromatin dynamics and the transcription of mobile genetic elements. AhR is also closely related to epigenetics, not only from the point of view of target gene expression but also with respect to its own regulation by promoter methylation. It is reasonable to consider that deregulation of these many functions could have a causative role, or at least contribute to, human disease. Consequently, several laboratories have proposed that AhR could be a valuable tool as diagnostic marker and/or therapeutic target in human pathologies. An additional point of interest is the possibility of regulating AhR activity by endogenous non-toxic low weight molecules agonist or antagonist molecules that could be present or included in the diet. In this review, we will address these molecular and functional features of AhR biology within physiological and pathological contexts.